Editorial Team - Drug Analytical Research (Drug Analytical Research, 2026)
When launching the seventh issue of Drug Analytical Research, the editorial team would like to express its satisfaction with the continuous evolution with the scientific and academic community. Even in a period of uncertainties due to the Coronavirus epidemic, which affects different areas on the world stage, this periodical maintains its mission to spread knowledge and research in the analytical area of drugs and medicines. In this context, we are grateful for the contribution of authors who play a fundamental role in the journal’s growth trajectory, providing a plurality of subjects in analytical research.